RIGID-FLEXIBLE COUPLING DYNAMICS OF COAL WINNING MACHINE CUTTING PART DRIVE SYSTEM SIMULATION - MAO Jun; LIU XiaoNing; CHEN HongYun; SONG QiuShuang; YUAN Zhi (Jixie qiangdu)
On the basis of the theory of rigid-flexible coupling multibody dynamics as well as the transmission system of coal winning machine cutting part the transmission principle and structure parameters,the dynamic characteristics of coal winning machine cutting part drive system was researched for the problem about dynamic characteristics of coal winning machine cutting part the transmission system. The rigid-flexible coupling dynamics model of coal winning machine cutting part for gear transmission system was built in Recurdyn software environment. To the cutting force in drum three loads,Transmission Model was under full consideration of the flexible drive shaft in all directions feature and calculated the gear meshing force,strain and bearing junctioncontact. Results showed that 11 th gear mesh together is the biggest,11272634. 4N. The maximum contact force,912317. 98 N,is measured at the place of the shaft 5 bearings 1. Results provide a basis for optimum design of the transmission system and prediction of fatigue life.